Transformation of sodium bicarbonate and CO2 into sodium formate over NiPd nanoparticle catalyst - Wang, Mengnan; Zhang, Jiaguang; Yan, Ning (Frontiers in Chemistry, 2013)
The present research systematically investigated, for the first time, the transformation of sodium bicarbonate and CO2 into sodium formate over a series of Ni based metal nanoparticles (NPs). Ni NPs and eight NiM (M stands for a second metal) NPs were prepared by a facile wet chemical process and then their catalytic performance were evaluated in sodium bicarbonate hydrogenation. Bimetallic NiPd NPs with a composition of 7:3 were found to be superior for this reaction, which are more active than both pure Ni and Pd NPs. Hot filtration experiment suggested the NPs to be the truly catalytic active species and kinetic analysis indicated the reaction mechanism to be different than most homogeneous catalysts. The enhanced activity of the bimetallic nanoparticles may be attributed to their smaller size and improved stability.